2017
DOI: 10.1007/s00125-017-4492-z
|View full text |Cite
|
Sign up to set email alerts
|

A Coxsackievirus B vaccine protects against virus-induced diabetes in an experimental mouse model of type 1 diabetes

Abstract: Aims/hypothesis Epidemiological studies suggest a role for Coxsackievirus B (CVB) serotypes in the pathogenesis of type 1 diabetes, but their actual contribution remains elusive. In the present study, we have produced a CVB1 vaccine to test whether vaccination against CVBs can prevent virus-induced diabetes in an experimental model. Methods NOD and SOCS1-tg mice were vaccinated three times with either a formalin-fixed non-adjuvanted CVB1 vaccine or a buffer control. Serum was collected for measurement of neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 11 publications
0
65
0
Order By: Relevance
“…Effective and safe vaccines have been developed against polioviruses and enterovirus 71, but there are no vaccines available for the enteroviruses linked to type 1 diabetes. Recent preclinical studies provided proof-of-concept that a CVB vaccine prevents viral infection and diabetes induction in mice harbouring beta cells genetically permissive to CVB infection [ 52 ]. It is critical to determine which virus serotypes are associated with type 1 diabetes in different geographical regions over various periods.…”
Section: Rationale For the Development Of A Vaccinementioning
confidence: 99%
“…Effective and safe vaccines have been developed against polioviruses and enterovirus 71, but there are no vaccines available for the enteroviruses linked to type 1 diabetes. Recent preclinical studies provided proof-of-concept that a CVB vaccine prevents viral infection and diabetes induction in mice harbouring beta cells genetically permissive to CVB infection [ 52 ]. It is critical to determine which virus serotypes are associated with type 1 diabetes in different geographical regions over various periods.…”
Section: Rationale For the Development Of A Vaccinementioning
confidence: 99%
“…Recently, further collaboration studies were set out to test whether the inactivated CVB vaccine preventing CVB infection could also prevent virusinduced diabetes in mice. These studies first confirmed that CVB infection can accelerate diabetes onset in NOD and SOCS-1-Tg mice and then proved that the CVB vaccine protects not only from CVB infection but also against CVB-induced diabetes development in SOCS-1-Tg mice [110].…”
Section: Preclinical Development Of a Cvb Vaccine Against T1dmentioning
confidence: 69%
“…In a followup study, the vaccine was tested on suppressor of cytokine signaling transgenic (SOCS1-tg) mice, in which beta cells are unable to respond to IFNs and have an increased susceptibility to EV infection [80]. Similarly to NOD mice, SOCS1-tg mice developed a robust antibody response, were protected from a CVB1 challenge and from diabetes and had normal pancreas morphology [80]. The studies exposed above and the identification of different EVs serotypes with possible roles in T1D suggest that the development of an EVs vaccine for T1D could have great benefits, but could be challenging to produce.…”
Section: Calling For Reinforcements Co-operation Is the Keymentioning
confidence: 99%